2014
DOI: 10.1111/apm.12330
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of circulating CD4+CXCR5+ T cells in type 2 diabetes mellitus

Abstract: Type 2 diabetes mellitus (T2DM) is characterized by a chronic low-grade inflammatory state. Follicular helper T cells (Tfh) play critical roles in inducing B-cell activation and producing various cytokines, whereas circulating CD4+CXCR5+ T cells (CTfh) may act as a counterpart to measure Tfh cell disorders. In this study, we investigated whether Tfh could be involved in the development of T2DM by assessing CTfh in peripheral blood. CTfh and it subtypes were determined by measuring CD3, CD4, CXCR5, CXCR3, and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 21 publications
2
16
2
Order By: Relevance
“…Follicular B cells contributed the bulk of the IL-6 and IL-10 secreted by total B cells with marginal zone B cells contributing very little of either cytokine [86]. Circulating follicular T helper cells (CD4+ CXCR5+), which provide assistance to B cells, were also found to be increased in diabetic patients versus healthy controls [87]. …”
Section: The Adaptive Immune System In Irmentioning
confidence: 99%
“…Follicular B cells contributed the bulk of the IL-6 and IL-10 secreted by total B cells with marginal zone B cells contributing very little of either cytokine [86]. Circulating follicular T helper cells (CD4+ CXCR5+), which provide assistance to B cells, were also found to be increased in diabetic patients versus healthy controls [87]. …”
Section: The Adaptive Immune System In Irmentioning
confidence: 99%
“…Based on the evidence that the circulating CD4 + T cells play important roles in type 2 diabetes, we first analyzed the expression of Tim‐3 on peripheral CD4 + T cells in both the healthy donors and the type 2 diabetes patients by flow cytometry. As shown in Figure a, the type 2 diabetes patients ( n = 31, 17.26 ± 1.51%) have a much higher level of Tim‐3 on CD4 + T cells than healthy donors ( n = 18, 4.69 ± 0.45%).…”
Section: Resultsmentioning
confidence: 99%
“…M2 macrophages carry out tissue surveillance and remodeling functions, and are associated with maintaining insulin sensitivity 39 . Tim-3 promotes the macrophages to polarize to the M2 phenotype 28 . The results of the present study showed that type 2 diabetes patients have a much lower level of Tim-3 on monocytes (Figure 1a).…”
Section: Discussionmentioning
confidence: 99%
“…However, recent research has shown that T cells also play an important role in various steps in the development of T2DM. Dysregulation of CD4+CXCR5+ T cells and production of excessive proinflammatory cytokines may play an important part in the mechanism of chronic low-grade inflammation of insulin resistance[ 4 , 23 ]. The increased risk of T2DM due to TCR repertoire variation also implicates a role for autoimmunity[ 24 ].…”
Section: Discussionmentioning
confidence: 99%